2023
DOI: 10.1111/sum.12877
|View full text |Cite
|
Sign up to set email alerts
|

Effect of straw biochar application on soil carbon, greenhouse gas emissions and nitrogen leaching: A vegetable crop rotation field experiment

Abstract: Intensive vegetable crop systems are rapidly developing, with consequences for greenhouse gas (GHGs) emissions, nitrogen leaching and soil carbon. We undertook a field trial to explore the effect of biochar application (0, 10, 20 and 40 t ha−1) on these factors in lettuce, water spinach and ice plant rotation. Our results show that the 20 and 40 t ha−1 soil treatments resulted in the SOC content being 26.3% and 29.8% higher than the control (0 t ha−1), respectively, with significant differences among all treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…The most significant reduction was seen in soils amended with sugarcane straw biochar, where N2O emissions were 50% lower than in NF (Figure 12 B). This finding corroborates with studies that have observed suppression of N2O emissions caused by straw-based biochars (Abbruzzini et al, 2019;Hamad et al, 2023;Zhang et al, 2022). Conversely to previous studies that reported no reductions in soil N2O emissions in response to woody biochar application (Lan et al, 2019;Ramlow et al, 2019), we observed that both wood-based biochars reduced N2O emissions.…”
Section: Discussionsupporting
confidence: 92%
“…The most significant reduction was seen in soils amended with sugarcane straw biochar, where N2O emissions were 50% lower than in NF (Figure 12 B). This finding corroborates with studies that have observed suppression of N2O emissions caused by straw-based biochars (Abbruzzini et al, 2019;Hamad et al, 2023;Zhang et al, 2022). Conversely to previous studies that reported no reductions in soil N2O emissions in response to woody biochar application (Lan et al, 2019;Ramlow et al, 2019), we observed that both wood-based biochars reduced N2O emissions.…”
Section: Discussionsupporting
confidence: 92%